A computational case study on the thermal performance of a rectangular microchannel having circular pin-fins - Mahdi Tabatabaei Malazi; Kenan Kaya; Ahmet Selim Dalkılıç (Case Studies in Thermal Engineering, 2023)
This paper concerns the hydraulic and thermal performances of a three-dimensional rectangular microchannel with circular pin-fins. Laminar flow with Reynolds values (Re) between 50 and 150 was investigated. A total of 20 cases were considered. Fifteen of them were carried out for circular pin-fins with 3 fin spacing-to-fin diameter ratios (l/d = 2, 4, and 6) and 5 Re values (Re = 50, 75, 100, 125, and 150) for a constant fin height-to-channel height ratio (h/H = 0.25). The others were run without the use of circular pin-fins in the computational domain. The pressure drop and velocity distribution contour plots were obtained. Average outlet temperature and average Nusselt number (Nu) were used to study microchannels’ thermal performances. The validation process was performed for the Nu and friction factor, with absolute errors of less than 2% and 7%, respectively. The increase in Re and decrease in fin spacing caused an increase in Nu and a decrease in average outlet temperature. The pressure drop increased with increasing Re and number of fins. Therefore, thermal and hydraulic performances were found to depend on them. The predicted results indicated that the maximum average outlet temperature, pressure drop, and Nu were obtained for the smallest l/d. Comparing the microchannel with l/d = 2 to the microchannel without fins for Re = 150, the average outlet temperature of the microchannel with l/d = 2 is increased by nearly 0.23%. At Re of 150, the pressure decrease in the microchannel with l/d = 2 is nearly 23% greater than in the microchannel without fins. The average Nu of the microchannel with l/d = 2 is approximately 9% greater than that of the microchannel without fins when the Re is 150.